Bimtek Penyusunan E-Asesmen Literasi Sains Berbasis AKM Bagi Guru IPA SMP Di Kota Bogor, Kabupaten Bogor Dan Kabupaten Sukabumi - Dwi Pursitasari, Indarini; Ahmadi, Enang (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Literacy skills for science teachers are needed to be skilled in facilitating the development of student literacy. The empowerment activity carried out aims to improve the ability of junior high school science teachers in Bogor Regency in compiling science literacy e-assessments based on the Minimum Competency Assessment (AKM). The participants were teachers who were members of the MGMP (Subject Teachers' Conference) in Bogor Regency. The activity was carried out in the form of Technical Guidance for 4 days followed by independent assignments. The ability or understanding of teachers towards assessment and science literacy was carried out through pretests and posttests. At the end of the activity, participants provided an assessment of the implementation of the technical guidance that had been held. The results of the activity showed an increase in teachers' understanding of assessment and science literacy with an N-gain achievement of 61.1% and teachers gave a very good assessment both in terms of organizing activities to prepare a science literacy e-assessment based on the Minimum Competency Assessment (AKM). The conclusion of this empowerment activity is that the training in compiling science literacy e-assessments has been able to improve teachers' skills in developing science-based assessment tools.